Early Childhood Literacy Development in Kindergarten - Rosimah, Rosimah; Mahluddin; Husin (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the development of early childhood literacy at TK Islam Muslimat in Jambi City, covering the school’s literacy environment and policy, the role of teachers, children’s literacy attainment, instructional methods and media, and parental involvement and evaluation. Early literacy is a crucial foundation for children’s reading and writing readiness and for their academic success at subsequent levels. A quantitative descriptive approach was employed. Data were collected through a 40-item questionnaire using a five-point Likert scale completed by eight purposively selected informants, namely the school principal, group B teachers, and parents/guardians, and were complemented by documentary study. The data were analyzed using descriptive statistics, including frequency distribution, mean scores, and achievement levels, and were then interpreted using five interpretive categories. The findings show that children’s literacy development is in the very good category, with a mean score of 4.25 (84.9%). The aspect of children’s literacy attainment obtained the highest score (4.42), whereas the aspect of instructional methods and media obtained the lowest score (3.98), although it remained in the good category. This study contributes an empirical portrait of contextual, Islamic-value-based literacy practices in an early childhood education unit that may serve as a reference for developing comparable literacy programs.